Accounting and management practices in the third sector in Angola - Paiva, I.; Carvalho, L. (Economics and Sociology, 2018)
This study seeks to analyse the relationship between accounting and management practices in organisations of the third sector in a less developed country, taking regional differences into account. Primary data were collected using a survey conducted among the third sector organisations in the provinces of Huila, Benguela, Huambo and Namibe. The results of the study identify a relationship between the type of organisation and the origin of the resources obtained, the disclosure of financial statements, the use of operational plans and the use of budgets. This exploratory study contributes to the research on accounting and management in the third sector in that it is pioneering in the analysis of simultaneous influence of accounting and management characteristics in the four studied regions of Angola.